2023
DOI: 10.24953/turkjped.2022.1021
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of extremely low birth weight infants in a tertiary neonatal intensive care unit in Türkiye

Abstract: Background. Advances in neonatal care have led to increased survival of extremely preterm infants. Extremely low-birth-weight (ELBW) infants, defined as infants weighing less than 1000 g at birth, constitute a significant portion of neonatal intensive care unit (NICU) patients. The aim of this study is to determine the mortality and short-term morbidities of ELBW infants and assess the risk factors related to mortality. Methods. The medical records of ELBW neonates hospitalized in the NICU of a tertiary-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We did not observe any significant improvements in PVL (8.1%), NEC at all stages (22.8%), PDA (31.5%), sepsis/probable sepsis (21.5%), and ROP ≥ 2 (18.1%) rates between study periods. A Turkish study reported rates of severe IVH of 14.5%, severe NEC of 4.6%, PDA of 50.7%, late-onset sepsis of 24.0%, and severe ROP of 13.3% among ELBW infants between 2017 and 2021 [33].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any significant improvements in PVL (8.1%), NEC at all stages (22.8%), PDA (31.5%), sepsis/probable sepsis (21.5%), and ROP ≥ 2 (18.1%) rates between study periods. A Turkish study reported rates of severe IVH of 14.5%, severe NEC of 4.6%, PDA of 50.7%, late-onset sepsis of 24.0%, and severe ROP of 13.3% among ELBW infants between 2017 and 2021 [33].…”
Section: Discussionmentioning
confidence: 99%
“…ELBW infants exhibit distinctive growth patterns and developmental trajectories that demand close attention. (1)(2)(3)(4)(5) The significance of studying the postnatal growth of ELBW infants is underscored by a body of research that highlights the distinctive features of their growth patterns, nutritional requirements, and long-term consequences. Various studies have shed light on the challenges associated with ELBW infants' growth and the interventions aimed at mitigating them.…”
Section: Introductionmentioning
confidence: 99%